2019
DOI: 10.3389/fimmu.2019.00318
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Dysfunction Associated With Aging and Autoimmune Diseases

Abstract: Impaired humoral responses, as well as an increased propensity for autoimmunity, play an important role in the development of immune system dysfunction associated with aging. Accumulation of a subset of atypical B cells, termed age-associated B cells (ABCs), is one of the key age-related changes in B cell compartments. ABCs are characterized by their distinct phenotypes, gene expression profiles, special survival requirements, variations in B cell receptor repertoires, and unique functions. Here, we summarize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(132 citation statements)
references
References 57 publications
(96 reference statements)
5
126
0
1
Order By: Relevance
“…B lymphocytes produce different types of antibodies for eliminating of challengers. Additionally, B lymphocytes have an important role in the immune system through the presentation of antigens and secretion of cytokines [103]. B lymphocytes arising from hematopoietic stem cells in the bone marrow as pro-B lymphocytes.…”
Section: Aging and Immune-senescencementioning
confidence: 99%
“…B lymphocytes produce different types of antibodies for eliminating of challengers. Additionally, B lymphocytes have an important role in the immune system through the presentation of antigens and secretion of cytokines [103]. B lymphocytes arising from hematopoietic stem cells in the bone marrow as pro-B lymphocytes.…”
Section: Aging and Immune-senescencementioning
confidence: 99%
“…This Review focuses on clones of myeloid cells that increase with ageing and how these clones contribute to atherosclerosis. We do not describe how ageing affects other cells of the immune system, which has been reviewed previously (for example, B cells 20 , T cells 21 , eosinophils or dendritic cells 22 ). In addition, we focus on vascular mitochondrial function and how mitochondrial dysfunction could influence inflammatory pathways within the vasculature.…”
Section: Introductionmentioning
confidence: 99%
“…However, no sufficient data exists for the effect of age on the risk of developing SARDs; our study demonstrated that the presence of the leptospiral infection in elderly with SARDs. The mechanism may be due to abnormalities of the host immune response, particularly immune senescence, resulted in many inflammatory responses, increasing susceptibility to infections, and enhancing the production of autoantibodies 33 . Another possible explanation is the expansion of many protective regulatory mechanisms in the elderly (e.g., higher production of peripheral T-regulatory cells), resulting in higher autoimmunity but yet a lower prevalence of autoimmune diseases 34 .…”
Section: Discussionmentioning
confidence: 99%